Iridium‐Catalyzed Enantioselective Unbiased Methylene C(sp3)–H Borylation of Acyclic Amides. Issue 7 (14th December 2020) - Yang, Yuhuan; Chen, Lili; Xu, Senmiao
Abstract: We herein report amide directed enantioselective β‐C(sp 3 )−H borylation of unbiased methylene C−H bonds of acyclic amides enabled by iridium catalysis for the first time. The key to the success of this transformation relies on the careful selection of the combination of iridium precursor and chiral bidentate boryl ligands. A variety of functional groups are well‐tolerated, affording chiral β‐functionalized amides in good to excellent enantioselectivities. We also demonstrate the application of the current method by stereospecific conversion of C−B bond into other functionalities. Abstract : Borylating the Inert C−H Bonds: a chiral bidentate boryl ligand (CBL ) for the first time enables iridium‐catalyzed enantioselective borylation of unbiased methylene β‐C(sp 3 )−H bonds, furnishing a vast array of β‐functionalized chiral amides with up to >99 % ee value.